Nickel Salt Dependency as Catalyst in the Plating Bath on the Film Properties of Cu/Cu-Ni - Rosyidan, Cahaya; Kurniawan, Budhy; Soegijono, Bambang; Maulani, Mustamina; Samura, Lisa; Nababan, Frederik Gresia; Putra, Valentinus Galih Vidia; Susetyo, Ferry Budhi (Science and Technology Indonesia, 2024)
Metal plating frequently employs nickel (Ni) and copper (Cu) as anodes. Cu/ Cu-Ni film formed has many advantages, such as better corrosion resistance and high hardness characteristics. This study aims to assess the properties of Cu/Cu-Ni film, such as phase, surface morphology, crystallographic orientation, hardness, corrosion analysis, and contact angle, which were fabricated using electrodeposition with various Ni salt additions (0.3, 0.5 and 0.7 M). In addition, the cathode current efficiency (CCE) and deposition rate of the Cu/Cu-Ni electrodeposition were also investigated. An increase in Ni salt in the plating bath could enhance the pH, promoting higher CCE and depleting hydrogen evolution at the cathode, leading to the presenting Ni phase in the alloy. The higher concentration of Ni salt in the solution could also enhance the deposition rate due to a shift to a pH value, which affects the roughening of the surface morphology, promoting a higher contact angle. All crystal structures generated by Cu/Cu-Ni electrodeposition were FCC, with the preferred orientation of the (111) plane. Crystallite size and lattice strain depend on the deposition rate. Less crystallite size and lattice strain affect the film’s hardness and corrosion resistance. Moreover, the third bath had the resulting Cu-Ni layer with the best hardness and corrosion rate of around 136 HV and 0.081 mmpy.